6 - Citizenship and Rights: The Failures of the Post-colonial State in Africa: 10.4314/ad.v28i1.22172 - Kanyinga, Karuti (Africa Development, 2002)
hroughout Africa, economic and political reforms introduced to resuscitate 'development' have failed to facilitate growth. Inequalities and poverty have continued to deepen and there is unprecedented reproduction of parochial identi ties and local social conflicts. Social citizenship itself is in a crisis: there is mass disempowerment and dispossession of ordinary citizens through loss of means of livelihood. The refonns have generally failed to promote and safeguard citizens' interests. This article examines how popular struggles for social citizenship and in particular struggles for protection of social-economic rights are organized and sus tained and the challenges they experience in this regard. The new forms of inter action between the state, the peasants and the markets are also discussed. The article is based on findings of a study on Mwea rice irrigation scheme in Kenya. The discussion concludes that the state remains an important actor in the local social-political and development space notwithstanding the reforms that have taken place. Politically and economically influential elites have control over local structures for development as well as popular organizations. This makes it difficult for consolidation of social citizenship. The crisis facing social citizenship therefore is bound to deepen if the reforms do not seek to democratize local level power structures simultaneous with democratization at the broader national level.